Alih Kode dan Campur Kode Dalam Interaksi Sosial Penjual dan Pembeli di Pasar Johar Karawang Serta Rekomendasinya Sebagai Handout Teks Negosiasi Kelas X - Natalia, Desvita; Setiawan, Hendra; Syafroni, Roni Nugraha (Jurnal Ilmiah Wahana Pendidikan, 2024)
The mixing of two or more languages in communication in everyday life to facilitate what is conveyed. This is what causes code switching and code mixing in language. Code-switching is the transition of one language to another, while code-mixing is the use of a language in which there are elements of another language. This research describes the forms and factors that cause code-switching and code-mixing in the social interaction of sellers and buyers at Johar Market in Karawang, and its recommendation as a handout for class X negotiation text. This research uses qualitative method. The data source used in this research is through social interaction between sellers and buyers in Johar Market, Karawang. Data collection techniques in this study used observation techniques, recording techniques, listening and recording techniques. Internal code switching and external code switching were found. Factors causing code switching, namely speaker factors, interlocutor factors, and factors that generate a sense of humor. The form of code mix is word form, phrase form, clause form, and word repetition form. The factors that cause code mixing are role factors and the desire to explain. Code-switching and code-mixing in social interactions at Johar Market in Karawang occur because sellers and buyers want to build closeness and fulfill each other's goals.